Variation in the strength of allometry drives rates of evolution in primate brain shape. Issue 1930 (8th July 2020) - Sansalone, G.; Allen, K.; Ledogar, J. A.; Ledogar, S.; Mitchell, D. R.; Profico, A.; Castiglione, S.; Melchionna, M.; Serio, C.; Mondanaro, A.; Raia, P.; Wroe, S.
Abstract : Large brains are a defining feature of primates, as is a clear allometric trend between body mass and brain size. However, important questions on the macroevolution of brain shape in primates remain unanswered. Here we address two: (i), does the relationship between the brain size and its shape follow allometric trends and (ii), is this relationship consistent over evolutionary time? We employ three-dimensional geometric morphometrics and phylogenetic comparative methods to answer these questions, based on a large sample representing 151 species and most primate families. We found two distinct trends regarding the relationship between brain shape and brain size. Hominoidea and Cercopithecinae showed significant evolutionary allometry, whereas no allometric trends were discernible for Strepsirrhini, Colobinae or Platyrrhini. Furthermore, we found that in the taxa characterized by significant allometry, brain shape evolution accelerated, whereas for taxa in which such allometry was absent, the evolution of brain shape decelerated. We conclude that although primates in general are typically described as large-brained, strong allometric effects on brain shape are largely confined to the order's representatives that display more complex behavioural repertoires.